Intraperitoneal Hydrocortisone plus Bupivacaine versus Bupivacaine alone for Pain Relief after Laparoscopic Cholecystectomy - Mahesh Sharma; Kalpana Kharbuja; Nil Raj Sharma (Journal of Lumbini Medical College, 2016)
Introduction: Laparoscopic cholecystectomy has been the gold standard in the treatment of gallstones since last decades. Beside several benefits of laparoscopic cholecystectomy compared with open surgery, postoperative pain is still a frequent melancholy.  Hence, pain management is utmost regarding patients' comfort. The main objective of the study was to compare the effect of intraperitoneal hydrocortisone plus bupivacaine with bupivacaine alone on pain relief following laparoscopic cholecystectomy.